Diagnostic Utility of the Ictal Cry - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Consecutive video-EEGs of 20 adult patients with generalized tonic-clonic (GTC) seizures and 20 with psychogenic nonepileptic seizures (PNES) were reviewed from the archives at University of South Florida, Tampa General Hospital, and the audio components of the recordings were analyzed and compared for all vocalizations.